Trifluoromethyl Fluorocoxib A Detects Cyclooxygenase-2 Expression in Inflammatory Tissues and Human Tumor Xenografts - Uddin, Md. Jashim (American Chemical Society, 2014)
[Image: see text] Fluorocoxib A is an effective COX-2-targeted optical imaging agent, used for in vivo detection of inflammatory tissues and premalignant and malignant tumors that express elevated levels of COX-2 (Uddin et al. Cancer Res. 2010, 70, 3618–3627). In an effort to discover novel optical probes for COX-2, a trifluoromethyl analogue of fluorocoxib A (CF(3)-fluorocoxib A) was synthesized and evaluated for its ability to inhibit COX-2 in vitro purified enzyme and human cancer cell lines. Kinetic analysis revealed that CF(3)-fluorocoxib A is a slow, tight binding inhibitor of COX-2 that exhibits low nanomolar inhibitory potency. While CF(3)-fluorocoxib A and fluorocoxib A are similar in structure, CF(3)-fluorocoxib A shows improved potency in inhibition of wtCOX-2 and with a series of site-directed COX-2 mutants. After intraperitoneal injection, selective uptake of CF(3)-fluorocoxib A is detected in inflamed mouse paws compared to noninflamed contralateral paws by optical imaging, and uptake is blocked by pretreatment with the COX-2 inhibitor, celecoxib. Selective uptake is also detected in the COX-2-positive human tumor xenografts (1483 HNSCC) as compared with the COX-2-negative tumor xenografts (HCT116) in an in vivo nude mouse tumor model. These in vitro and in vivo studies suggest that binding to COX-2 is the major determinant of uptake of CF(3)-fluorocoxib A into the inflamed tissues and tumor xenografts. Thus, this new COX-2-targeted imaging probe should find utility in the detection and evaluation of COX-2 status in naturally occurring malignancies.